Effects of Nicotine Exposure From Tobacco Products and Electronic Cigarettes on the Pathogenesis of Neurological Diseases: Impact on CNS Drug Delivery - Sharma, Sejal; Rahman Archie, Sabrina; Kanchanwala, Vrajesh; Mimun, Kyle; Rahman, Md Ashrafur; Zhang, Yong; Abbruscato, Thomas (Frontiers in Drug Delivery, 2022)
Nicotine, the major component of tobacco smoke (TS) and electronic cigarette (e-cig) vape, has been reported in some cases to be prodromal to cerebrovascular toxicity as well as a promoting factor for the onset of various neurological diseases. In some conditions, pre-exposure to nicotine can lead to a state of compromised blood-brain barrier (BBB) integrity, including altered BBB-related protein expression, BBB leakage, and defective ion and glucose homeostasis within the brain. Moreover, drugs used to treat central nervous system disorders (CNS) have been reported to interact with nicotine and other components of TS/e-cig through both transporter and enzyme-based mechanisms. Herein we discuss nicotine’s potential toxicity at the brain cerebrovasculature and explain how nicotine (from smoking/vaping) may interfere with the uptake of CNS drugs through a CNS drug interaction perspective.